DHW-221, a Dual PI3K/mTOR Inhibitor, Overcomes Multidrug Resistance by Targeting P-Glycoprotein (P-gp/ABCB1) and Akt-Mediated FOXO3a Nuclear Translocation in Non-small Cell Lung Cancer - Liu, Mingyue; Xu, Chang; Qin, Xiaochun; Liu, Wenwu; Li, Deping; Jia, Hui; Gao, Xudong; Wu, Yuting; Wu, Qiong; Xu, Xiangbo; Xing, Bo; Jiang, Xiaowen; et al. (Frontiers in Oncology, 2022)
Multidrug resistance (MDR) is considered as a primary hindrance for paclitaxel failure in non-small cell lung cancer (NSCLC) patients, in which P-glycoprotein (P-gp) is overexpressed and the PI3K/Akt signaling pathway is dysregulated. Previously, we designed and synthesized DHW-221, a dual PI3K/mTOR inhibitor, which exerts a remarkable antitumor potency in NSCLC cells, but its effects and underlying mechanisms in resistant NSCLC cells remain unknown. Here, we reported for the first time that DHW-221 had favorable antiproliferative activity and suppressed cell migration and invasion in A549/Taxol cells in vitro and in vivo. Importantly, DHW-221 acted as a P-gp inhibitor via binding to P-gp, which resulted in decreased P-gp expression and function. A mechanistic study revealed that the DHW-221-induced FOXO3a nuclear translocation via Akt inhibition was involved in mitochondrial apoptosis and G0/G1 cell cycle arrest only in A549/Taxol cells and not in A549 cells. Interestingly, we observed that high-concentration DHW-221 reinforced the pro-paraptotic effect via stimulating ER stress and the MAPK pathway. Additionally, intragastrically administrated DHW-221 generated superior potency without obvious toxicity via FOXO3a nuclear translocation in an orthotopic A549/Taxol tumor mouse model. In conclusion, these results demonstrated that DHW-221, as a novel P-gp inhibitor, represents a prospective therapeutic candidate to overcome MDR in taxol-resistant NSCLC treatment.